2014
DOI: 10.1007/s12015-014-9554-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture with Mature Islet Cells Augments the Differentiation of Insulin-Producing Cells from Pluripotent Stem Cells

Abstract: Islet transplantation has been hampered by the shortage of islet donors available for diabetes therapy. However, pluripotent stem cells (PSCs) can be an alternative source of insulin-producing cells (IPCs) because of their capacity for self-renewal and differentiation. We described a method to efficiently differentiate PSCs into IPCs by co-culturing mature islets with directed-differentiated pancreatic endoderm (PE) cells from mouse and human PSCs. PE cells co-cultured with islet cells or islet cell-derived co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…F127 is a nonionic surfactant that assists penetration of AM esters into cells. A low dose of F127 [0.1–0.15% (v/v)] was safely added to islets, as well as a β-cell line 14,18 , but in these studies, the effect on fluorescence was not quantified. We showed that 0.2% F127 enhances fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…F127 is a nonionic surfactant that assists penetration of AM esters into cells. A low dose of F127 [0.1–0.15% (v/v)] was safely added to islets, as well as a β-cell line 14,18 , but in these studies, the effect on fluorescence was not quantified. We showed that 0.2% F127 enhances fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays extensive research on the use of stem cell has shown a hope for cure of DM [21] [22]. Stem cells that have been investigated in the treatment of DM include pluripotent stem cells (PSCs), mesenchymal stem cells (MSCs) and embryonic stem cells (ESCs) [7] [21] [22].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells that have been investigated in the treatment of DM include pluripotent stem cells (PSCs), mesenchymal stem cells (MSCs) and embryonic stem cells (ESCs) [7] [21] [22].…”
Section: Discussionmentioning
confidence: 99%
“…Bea et al (2015) cultured pluripotent SCs in the presence of mature islet cells. They found that the paracrine effects of these cells could lead to an increase in the differentiation efficiency of the pancreatic endoderm (PE) cells into mature IPCs [28]. A study performed by Yilmaz et al (2015) revealed that the ESC coculture with mouse pancreatic islets resulted in higher differentiation efficacy toward IPCs [29].…”
Section: Coculture Methods Used For Differentiation Of Scs Intomentioning
confidence: 99%
“…They found that these cells normalized hyperglycemia in diabetic mice [35]. Another study on diabetic nude mice indicated that transplantation diabetic mice with IPCs derived from pancreatic stem cells cocultured with islet cells exhibited restored euglycemia and improved glucose tolerance [28]. Qu et al (2014) also revealed that administration of laminin 411-induced IPCs rapidly and significantly downregulated fasting blood glucose levels, significantly reduced the HbA 1 c concentration, and markedly improved the symptoms and survival of diabetic rats [32].…”
Section: Use Of In Vivo Microenvironmental Simulation Formentioning
confidence: 99%